2015
DOI: 10.1177/0363546515614585
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Lateral Ankle Sprains in Football Players Based on Clinical Tests and Body Mass Index

Abstract: Low performance on the SEBT-ANT predicted a risk of LAS in football players. BMI was also significantly higher in football players who sustained an LAS. Identifying clinical tools for successful LAS injury risk prediction will be a critical step toward the creation of effective prevention programs to reduce risk of sustaining an LAS during participation in football.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
86
4
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 42 publications
6
86
4
10
Order By: Relevance
“…The star excursion balance test (SEBT) is a well-established, reliable clinical tool for dynamic postural control [3] that assesses different neuromuscular functions, such as proprioception [4], joint range of motion (ROM) [5] and lower extremity strength and balance [6]. Clinically, the SEBT has proved to be sensitive in detecting functional deficits in patients with different lower extremity dysfunctions and diagnoses [3], improvements in response to training [7], and predicting the risk of lower extremity injuries [8]. However, the SEBT does not examine trunk, upper extremity and all hip joint movements in the assessment of dynamic postural control, and therefore is not well suited to revealing functional deficits in these joints in combination with lower extremity joint movements.…”
Section: Introductionmentioning
confidence: 99%
“…The star excursion balance test (SEBT) is a well-established, reliable clinical tool for dynamic postural control [3] that assesses different neuromuscular functions, such as proprioception [4], joint range of motion (ROM) [5] and lower extremity strength and balance [6]. Clinically, the SEBT has proved to be sensitive in detecting functional deficits in patients with different lower extremity dysfunctions and diagnoses [3], improvements in response to training [7], and predicting the risk of lower extremity injuries [8]. However, the SEBT does not examine trunk, upper extremity and all hip joint movements in the assessment of dynamic postural control, and therefore is not well suited to revealing functional deficits in these joints in combination with lower extremity joint movements.…”
Section: Introductionmentioning
confidence: 99%
“…The current gold standard balance protocol is the 'Y-Balance Test' for the lower quarter (YBT-LQ) [10,15]. The test was originally developed from the Star Excursion Balance Test (SEBT) with the aim to objectify the pass/fail criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Large bodies of research have demonstrated dynamic balance deficits, as measured by the SEBT, between control and pathological groups with conditions such as acute ankle injuries (Doherty et al, 2015), chronic ankle instability and anterior cruciate ligament injuries (Herrington et al, 2009). Additionally, researchers have attempted to establish the role these assessments play in the detection of risk factors that may predispose individuals to lower limb injuries (Gribble et al, 2015, Plisky et al, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, researchers have attempted to establish the role these assessments play in the detection of risk factors that may predispose individuals to lower limb injuries (Gribble et al, 2015, Plisky et al, 2006. Despite this, there are a number of limitations to the SEBT which should be considered.…”
Section: Introductionmentioning
confidence: 99%